Peran Sistem Informasi pada peningkatan efektifitas kerja pegawai - Dwi Wahyudi; Pieter Sahertian; Endi Sarwoko (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
The purpose of the study was to analyze the role of information systems consisting of system quality, information quality, ease of use, and user satisfaction on information systems on the effectiveness of employees' work. The study population was 221 employees at the University of PGRI Kanjuruhan Malang, the number of samples in the study was 69 employees using the proportional random sample technique. The data analysis technique used multiple linear regression analysis. The results showed that the system quality, information quality, ease of use and user satisfaction had an effect on employee work effectiveness. So the information system will simplify and speed up the implementation of the work if the quality of the system is considered, the quality of information, the ease of use, and ensures that users are satisfied. Research is limited to one organization, can be developed by involving broader research